The Use of Digitalization Technology In The Cirebon City Resort Police To Fulfill Services To The Community - Destiana, Anggie; Nurhaliza, Intan; Mariska, Nevi; Heryanto, Yanto (Green Publisher Indonesia, 2024)
This journal is entitled The Use of Digitalization Technology in the Cirebon City Resort Police to Fulfill Services to the Community. Technological developments have brought changes in the public service process, including in the preparation of Police Record Certificates (SKCK). The introduction of the PRESISI POLRI application as an online platform for the creation of SKCK has increased the efficiency and accessibility of services. This research aims to be a means and forum for information in online SKCK making services to increase public trust in police institutions and optimize performance in law enforcement as a form of improving the quality of public services and realizing integrated Porli public services. This study uses a qualitative method through a descriptive approach by taking the research location at the Cirebon City Resort Police. The data collection technique involves triangulation, which is the combination of several methods such as observation, interviews and documentation. The results of this study have four dimensions to measure effectiveness, namely the accuracy of program goals, program socialization, program objectives and program monitoring. The results of this study show that the effectiveness of the SKCK making program through the PRESISI Application has not been fully effective. Socialization of the application is still not optimal, causing some people to not understand or use the application. The evaluation of the effectiveness of the program showed that while the application has been successful in achieving the accuracy of the goals and monitoring of the program, there are still shortcomings in the socialization and achievement of the program objectives. This research highlights the need for further efforts in wider and sustainable socialization, as well as increased efficiency in the process of making online SKCK